Modern Colloquial Eastern Elamite - McAlpin, David (Al-Burz, 2022)
This paper is a formal demonstration of cognation between Elamite, a major language of the ancient Near East, and Brahui, a language of Balochistan, spoken primarily in Pakistan but also in Iran and Afghanistan. It is identifying Brahui as Modern Colloquial Eastern Elamite. Almost exactly two millennia have elapsed between the last recording of Elamite and the first recorded example of Brahui. While closely related, Brahui is not a descendant of classical Elamite. Rather, it is descended from an unattested eastern branch of Elamite. Part, one deals with a full statement of the Comparative Method focusing on the root syllable. Part Two adds comparative morphology and retailed comparisons of the verb structure.